The use of β2-agonist therapy before hospital attendance for severe asthma exacerbations: a post-hoc analysis - Patel, Mitesh; Pilcher, Janine; Hancox, Robert J.; Sheahan, Davitt; Pritchard, Alison; Braithwaite, Irene; Shaw, Dominick E.; Black, Peter; Weatherall, Mark; Beasley, Richard (Nature Publishing Group, 2015)
Background: Patterns of inhaled β2-agonist therapy use during severe asthma exacerbations before hospital attendance are poorly understood.